Edukasi Pencatatan Keuangan Sederhana Berbasis Kas Untuk Santri Pesantren Quantum Idea - Yolifiandri Yolifiandri; Islamiah Kamil; Erfiana Wahyuningsih; Sri Anjarwati (Politeknik Penerbangan Indonesia Curug, 2026)
In today's era, Islamic boarding school students not only need to understand religious knowledge but also need to have the ability to manage finances to be more independent in the future. Quantum Idea Islamic Boarding School on Jl. Camar No. 101, Jatiraden Village, Jatisampurna District, Bekasi City, West Java, is committed to equipping its students with character education, entrepreneurship, and practical skills. This Simple Cash-Based Financial Recording Education Program emerged because many students are enthusiastic about entrepreneurship but still struggle to record and manage their finances properly. A lack of understanding of financial literacy makes it difficult to monitor cash flow, profits, and capital. However, accurate cash recording is essential for the stable and sustainable running of Islamic boarding school businesses. The goal of this activity is to improve students' ability to understand the basic concepts of cash flow and create simple financial reports in accordance with sharia principles. Students will learn to record incoming and outgoing cash manually and digitally and apply financial planning for both business and personal needs. The activities were carried out in several stages: outreach, interactive training with examples of Islamic boarding school businesses, mentoring in practical recording, and evaluation of learning outcomes through pre- and post-tests.